Licenciatura em matemática na modalidade de educação a distância: um desafio para a formação de professores - Athias, Miguel Fortunato (2010)
The aim of this paper is to discuss opportunities and prospects for training teachers of mathematics in the distance education mode. It builds on the experiences of two institutions of higher education, one with extensive experience in distance education, and the other developing a pilot project to be implemented later on a larger scale. It discusses the methods of distance learning that were held in the world and still are, they fit the courses surveyed could be included, the definitions of distance education that have been built over the time and what is the definition provided by law in Brazil; it debates also the tasks that teachers can take in this area and analyzes the curriculum of each course. This is a qualitative research, with characteristics presented by Lüdke and Andre (1986), which uses document analysis and interviews that were conducted with coordinators and teachers from different disciplines and the analysis of the interviews are based on the lessons of Bardin (2010). The theoretical foundations were sought especially in the work of Otto Peters, Maria Luiza Belloni, Garcia Gouvêa, Regina Silveira Barros Leal and Marcelo de Carvalho Borba. The results show that it is possible to conduct a good quality course in Mathematics in distance education, that teachers have been successfully overcoming the problems encountered in developing their courses to distance with the use of audio visual technology and resources, but there is still great difficulties on the part of teachers and students at this new opportunity, especially in terms of understanding of the peculiarities of distance education and the real role of teachers and students in this initial training